A computational examination of the therapeutic advantages of fourth-generation ALK inhibitors TPX-0131 and repotrectinib over third-generation lorlatinib for NSCLC with ALK F1174C/L/V mutations - Balasundaram, Ambritha; Doss, George Priya C. (Frontiers in Molecular Biosciences, 2024)
Background: In non-small cell lung cancer (NSCLC), a pivotal factor in promoting cancer development is the rearrangement in the anaplastic lymphoma kinase (ALK) gene, resulting in elevated ALK protein expression. F1174C/L/V is the acquired secondary resistant mutation in ALK. Significant survival improvements have been seen while tyrosine kinase inhibitors (TKIs) specifically target ALK. Nevertheless, the emergence of drug resistance hinders the clinical effectiveness of these drugs. Objective: This research sought to find the binding affinity/inhibitory effects of the existing lorlatinib (LOR) and upcoming TPX-0131 (Zotizalkib/TPX) and Repotrectinib (TPX-0005/REP) inhibitors against ALK F1174C/L/V mutations using computational approaches to identify potential strategies over resistance. Methods: We conducted molecular docking, molecular dynamics simulations (MDS), and MMPBSA calculations to investigate how compact macrocyclic inhibitors, such as TPX-0131 and Repotrectinib, fit within the ATP-binding boundary differ from Lorlatinib. Results: Our results demonstrated that the TPX-0131 and Repotrectinib contributed to higher binding energy in F1174C and F1174L mutations than lorlatinib. Repotrectinib showed greater binding energy in the F1174V mutation, whereas Lorlatinb and TPX-0131 exhibited similar binding energy. However, all three inhibitors showed significant binding energy towards the F1174C/L/V mutations found in NSCLC. Conclusion: This comparative study of the potential binding effects of fourth-generation inhibitors TPX-0131 and Repotrectinib and third-generation inhibitor lorlatinib for ALK F1174C/L/V mutations revealed the atomistic insights of the binding mechanism. These computational findings enable us to do further research for the clinical implementation of fourth-generation ALK inhibitors on ALK-positive NSCLC.